Prevalence, incidence, and mortality rates of breast cancer in Kazakhstan: data from the Unified National Electronic Health System, 2014–2019 - Midlenko, Anna; Mussina, Kamilla; Zhakhina, Gulnur; Sakko, Yesbolat; Rashidova, Gyunel; Saktashev, Bolat; Adilbay, Dauren; Shatkovskaya, Oxana; Gaipov, Abduzhappar (Frontiers in Public Health, 2023)
Background: Although there are numerous sources of epidemiologic information on breast cancer in Kazakhstan, none of them specifically examine the burden of this disease. Therefore, this paper aims to provide an overview of the breast cancer prevalence, incidence, mortality, distributions and changes over time in Kazakhstan based on nationwide large-scale health-care data from the national registry, in order to encourage more research on the impact of various diseases at the regional and national levels. Methods: The study cohort included all adult women aged more than 25 years old who were diagnosed with breast cancer in any clinical setting of the Republic of Kazakhstan during the period of 2014–2019. The data was extracted from the Unified Nationwide Electronic Health System (UNEHS) to apply a descriptive, incidence, prevalence and mortality rates calculations and Cox proportional hazards regression model. All survival functions and factors associated with mortality were tested for significance. Results: The cohort population (n=55465) with the age at diagnosis of breast cancer cases ranges from 25 to 97 years with a mean of 55.7±12.0 years. The majority of the study population is the age group 45-59 years, which is 44.8 % of the cohort. All-cause mortality for the cohort is 16%. Prevalence rate increased from 30.4 in 2014 per 10 000 population to 50.6 in 2019. The incidence rate varied from 4.5 per 10000 population in 2015 to 7.3 in 2016. Mortality rates were stable high in the senile age patients (75-89 years old). Breast cancer mortality was positively associated in women who had been diagnosed with diabetes, HR 1.2 (95% CI 1.1–2.3), whereas it is negatively associated with arterial hypertension, HR 0.4 ( 95% CI 0.4–0.5). Conclusion: Overall, Kazakhstan is experiencing an increase in the incidence of breast cancer cases, but mortality rate have been started to decline. The switch to population mammography screening could reduce breast cancer mortality rate. These findings should be utilized to help Kazakhstan determine what cancer control priorities should be utilized, including the need to implement efficient and affordable screening and prevention programs.